Workout contribution to the productivity of thesis writing - Boleng, Lukas Maria; Babang, Veramyta Maria Martha Flora; Ladjar, Maria Andriani Barek; Siahaan, Jurdan Martin; Wijaya, I Nyoman Wahyu Esa; Neolaka, Erwin Sarnoto (Jurnal Cakrawala Pendidikan, 2024)
The study investigates how structured workout sessions influence the productivity of students in completing a thesis as the final assignment in the bachelor's degree. Eigh-semester students from the Physical Education study program participated, with one group engaging in a 30-minute workout over eight sessions and a control group of 15 students not participating in these sessions. Using observation and monitoring tools, the study assessed the impact of these workouts on thesis preparation. Regression analysis showed a determination coefficient (R') of 0.729, indicating that 72.9% of the productivity variance was due to the workout sessions. Additionally, a 32% increase in assignment progress was observed in the experimental group. These results demonstrate a strong correlation between regular workouts and increased productivity in completing final assignments, highlighting the benefits of incorporating physical activity into academic routines.